Literature Review: Some of TVET Area Will Be Eliminated Due to Industrial Revolution 4.0, is That True? - Syahril Chairani, Vici; Bruri, Mochamad; Minghat, Dahar (International Journal of Engineering and Technology, 2018)
The 4.0 industrial revolution that began to be known since 2011 in Germany had a significant influence on several aspects of the world. Automation and digitilization that comes through Industrial Revolution 4.0, forecasted will brought many impact to demand and skillset of occupation and industry. Even that change is expected to have a lot of impact on Technical Vocational Education and Training (TVET). As a vocational education that has the main objective to prepare graduates to be able to work and be accepted in the industrial world. The aim of this study firstly is to provide a view of the issue about job lost due to the industrial revolution 4.0, is true or not. Secondly is to give an overview about the TVET area that have most possibility impact to be eliminated due to industry 4.0. To overcome this, this paper will explain a literature study from journal articles, opinion papers, conceptual papers, research study, etc. were analyzed for content related to Industrial Revolution 4.0 and TVET. It was concluded that (1) Occupation will be transformed by automation due to Industrial Revolution 4.0, not eliminated; (2) There is no certainty about which areas on TVET will be lost, but the areas that have the risk of being automated in TVET high school in Indonesia are administration, tourism and health.Â  Â
Keywords: TVET; Industrial Revolution 4.0; Manufacturing; Robotics; Artificial Intelligence; Smart Factory.